The quadruple burden: Reproductive labor & prison visitation in Venezuela - Fischer-Hoffman, Cory (Punishment & society, 2022)
Utilizing the Feminist-Marxist lens of reproductive labor, I examine how the caring work and bodies of women who visit prisons are central to an analysis of the relationship of incarceration and social reproduction under capitalism. My research is based on participant observation and interviews with women prison visitors in 2014–2015 in Venezuela. I analyze how women bring food, clean laundry and otherwise approved items; they take long journeys, wait in lines for hours and pass through an invasive strip search so that they can visit their loved ones in prisons. This work is even more burdensome because the prisons operating under carceral self-rule—run by armed organizations of inmates through a de-facto privatization that centers not just survival but profit —fail to provide even the most basic necessities. I argue that the work of caring for a loved one in this context creates an additional burden on top of a job, housework, and community activism. This fourth shift requires that women’s labor be incorporated into a neoliberal carceral apparatus and also demonstrates that while the carceral zone is porous, the bodies of poor racialized women are used to enforce the prison border.